The Middle Maghreb Man, space, and integration - hasbaia, mohamed (The Algerian Historical Journal, 2026)
The Middle Maghreb isconsidered as a virgin land for historical, social, cultural and psychologicalstudiesbecauseitwas able to maintainitsbordersthroughout the Middle Ages, despite the changes in states and politicalentities. It exists in a strategicenvironment, between the eastern Maghreb and Morocco, and extendsfrom Tlemcen in the west to coasts of pune to the east and the most accurate marsa Alkhbarat the borders of ancient carthage, and eastern and western relief in the south, on the borderswithsub-saharanAfrica. The Middle Maghreb isdistinguished by itsnumerousnaturalresources and diverse wealth, which are reflected in all aspects of human life in thisextendeddomain, helpingit in itsvariousactivities.The important geographical location of the Middle Maghreb has playeditsrole as a linkbetween the capitals of the Islamic West and by movingtowards the center of trade, due to the expansion of urbanization and the diversity of roads. Several States wereestablished on itssoilduring the Middle Ages, such as the Rostemids, The Hammadites and The Almohads, whofavoredthis communication.